Mempersiapkan Blended Learning Melalui Pelatihan Pembuatan E-Modul untuk Guru Madrasah Tsanawiyah YAPPI Mulusan - Faradiba; Septina Severina Lumbantobing; Taat Guswantoro; Nya Daniaty Malau; Ngia Masta (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2020)
The utilization of e-module is infallible be required in blended learning approach. Nevertheless, the existence of e-modul has not been wide known among teachers. Therefore training on e-module design through SIGIL software for teachers in MTs YAPPI Mulusan been done, as community service (PKM) activity by Physics Education Study Programme, FKIP UKI. The survey questionnaire used to evaluated the participant satisfaction. The surveys finding including: 1) All participant strongly agree that the training was beneficial in learning activity; 2) As many 87,5% participant agree that SIGIL as uncomplicated software to design e-module, while only 50% participants strongly agree that SIGIL as up to date software; 3) As many 72,9% participant satisfy with the usability of e-modul produced; and 4) As many 95,6% participant satisfy with the trainer. Hence, this community service implemented quite well, likewise the expectation of e-module development be concerning to the blended learning preparation.